Climate Change Imaginaries? Examining Expectation Narratives in Cli-Fi Novels. (February 2016) - Whiteley, Andrea; Chiang, Angie; Einsiedel, Edna
A new generation of climate fiction called Cli-fi has emerged in the last decade, marking the strong consensus that has emerged over climate change. Science fiction's concept of cognitive estrangement that combines a rational imperative to understand while focusing on something different from our everyday world provides one linkage between climate fiction and science fiction. Five novels representing this genre that has substantial connections with science fiction are analyzed, focusing on themes common across these books: their framing of the climate change problem, their representations of science and scientists, their portrayals of economic and environmental challenges, and their scenarios for addressing the climate challenge. The analysis is framed through Taylor's ideas of the social imaginary and the sociology of expectations, which proposes that expectations are promissory, deterministic, and performative. The novels illustrate in varying ways the problems attending the science-society relationship, the economic imperatives that have driven the characters' choices, and the contradictory impulses that define our connections with nature. Such representations provide a picture of the challenges that need to be understood, but scenarios that offer possibilities for change are not as fully developed. This suggests that these books may represent a given moment in the longer trajectory of climate fiction while offering the initial building blocks to reconsider our ways of living so that new expectations and imaginaries can be debated and reconceived.